TECHNIQUE OF QUALITY CONTROL OF STRUCTURE OF TOOTH GEARS OF THE MOTOR AND TRACTOR MACHINERY TRANSMISSIONS - S. P. Rudenko; A. A. Shipko; A. L. Valko; N. P. Timoshenko (Литьë и металлургия)
The reactant for microstructure quality assurance of cemented layer and a core of transmissions gears of the motor and tractor technique, enabling to reveal and identify the structural components influencing working capacity of details, is offered.